A novel tissue-mimicking phantom for US/CT/MR-guided tumor puncture and thermal ablation. (31st December 2022) - Zhong, Xinyu; Zhou, Ping; Zhao, Yongfeng; Liu, Wengang; Zhang, Xinghao
Abstract: Aim: This study aimed to develop a novel tumor-bearing tissue phantom model that can be used for US/CT/MR-guided tumor puncture and thermal ablation. Methods: The phantom model comprised two parts: a normal tissue-mimicking phantom and a tumor-mimicking phantom. A normal tissue phantom was prepared based on a polyacrylamide gel mixed with thermochromic ink. Moreover, a spherical phantom containing contrast agents was constructed and embedded in the tissue phantom to mimic a tumor lesion. US/CT/MR imaging features and thermochromic property of the phantom model were characterized. Finally, the utility of the phantom model for imaging-guided microwave ablation training was examined. Results: The tumor phantom containing contrast agents showed hyper-echogenicity, higher CT numbers, and lower T2 signal intensity compared with the normal tissue phantom in US/CT/MR images. Consequently, we could locate the position of the tumor in US/CT/MR imaging and perform an imaging-guided tumor puncture. When the temperature reached the threshold of 60 °C, the phantom exhibited a permanent color change from cream white to magenta. Based on this obvious color change, our phantom model could clearly map the thermal ablation region after thermotherapy. Conclusions: We developed a novel US/CT/MR-imageable tumor-bearing tissue model that can be used for imaging-guided tumor puncture and thermal ablation. Furthermore, it allows visual assessment of the ablation region by analyzing the obvious color change. Overall, this phantom model could be a good training tool in the field of thermal ablation.